Fall risks and the related factors for the homebound older people with dementia: Evidence from East China - Dong, Xiaoxin; Liu, Guanjun; Yin, Xiaoxu; Min, Rui; Hu, Yueming (Frontiers in Public Health, 2022)
Purpose: Falls are a major public health problem, especially for older people. This research was aimed to give a direct illustration of falls risks among homebound dementia older people in China, and to identify risk factors associated with falls. Methods: In 2020, a questionnaire survey was conducted among 1042 elderly people over 60 years old in Ningbo, eastern China. Taking the morse elderly fall risk assessment scale result as the dependent variable, basic health problems, living environment problems, social support problems, and behavioral awareness issues were independent variables, then χ2 tests and four multivariate ordinarily ordered logistic regression models were performed. Results: This study included 931 patients with Alzheimer ' s disease (89.34%). People with severe dementia were the most (27.9%), 16.2% of older people had fallen in the past three months, and 16.8% of them were at high risk of falling. 80-90 years old, vascular dementia, marital status, and history of falls were risk factors for cognitive function in older people (P<0.05); the kinds of chronic diseases, the activities of daily living, living environment, caregiver burden, caregiver knowledge, results of the Cohen Mansfield Agitation Inventory, and the Clinical Dementia Rating are protective factors for the risk of falls in older adults (P<0.05). Conclusion: The risk of falling of homebound older people with dementia in China was high. Caregivers such as relatives need to pay attention to these risk factors and take appropriate measures to prevent falls.